Community Pharmacists’ Involvement in Research in the United Kingdom - Crilly, Philip (Pharmacy (Basel), 2017)
Puropse. To investigate the engagement of community pharmacists (CPs) with pharmacy research and identify barriers preventing them from doing so. In addition, to determine the training and research tools available to support CPs to take part in research. Methods. A questionnaire was designed and distributed to a sample of community pharmacies (n = 323) within five local authorities in England, and to a random sample of community pharmacies (n = 329) within Greater London in two stages. Descriptive statistics were used to analyse the data using Microsoft Excel. Following questionnaire completion, CPs were invited to take part in face-to-face and telephone interviews to further explore their views on research. Interviews were transcribed and analysed using coding and thematic analysis. Results. A total of 104 questionnaires were completed out of 652 distributed. Over half (56.7%) of respondents considered research to be important to their practice. Approximately 88% of respondents had completed some form of mandatory research in the past two years, while only 29% were involved in non-mandatory research. Over two-thirds (67.9%) wanted to engage with research in the future, with 22.2% of these being most interested in recruiting patients for research. Barriers to research included lack of time (90%) and lack of remuneration (60%). 20 community pharmacists were interviewed. Three themes were identified: 1. Interest in taking part in research; 2. Awareness, support and knowledge; 3. Resources as barriers. Conclusion. CPs recognise the importance of research in their current practice, however, the biggest barrier they face is time. Further training may be useful to ensure CPs are adequately prepared to undertake research activities.